Understanding adolescent consumption patterns and attitudes towards the “puff” on the path to a smoke-free generation: a 2022 French perspective - Cottin, Marin; Catellin, Marion; De Guiran, Elen; Miliani, Katiuska; Josseran, Loïc; Gautier, Sylvain (Frontiers in Public Health, 2024)
Purpose Tobacco use remains the leading preventable cause of death in France, with 75,000 deaths each year. France aims to reduce smoking and achieve a smoke-free generation by 2032. However, recent tobacco industry innovations which mainly target young people, could undermine this goal. The main objective of this study is to assess the knowledge and consumption patterns of the “puff” among French adolescents in 2022. Methods A cross-sectional study using a structured online survey on a representative sample of 400 adolescents aged 13 to 16 years was conducted from July 4th to 20th, 2022. Results Around 66% of adolescents reported having heard of the puff”, and one in ten having tried it. Slightly fewer of them have tried cigarettes; 89.6% of experimenters reported that it allowed them to explore unique flavors, 81.9% found it fun to play with the puff-cloud, and 94.5% of regular consumers considered it a stylish or cool product. 76% of adolescents believe that the puff is dangerous to their health, 71.6% describe it as a polluting device, and 62.8% think it’s a gadget. Conclusion The “puff” is widely known by French adolescents and more commonly used than cigarettes, due, in part, to marketing specifically designed to target youth. That is why it could represent a threat to the smoke-free generation objectives. Public health policy could be informed by the ecological awareness of adolescents as a new lever of counter-influence to prevent this kind of consumption, as did ACT with the #stopcigarettespollution prevention campaign.